Development of Briquette from Coir Dust and Rice Husk Blend: An Alternative Energy Source - Md. Hamidul Islam; Md. Mosharraf Hossain; Md. Abdul Momin (Center of Biomass & Renewable Energy (CBIORE), 2014)
Biomass is one of the predominant renewable energy sources and the use of biomass for the energy generation has got much attention due to its environmental friendliness. Densification of coir dust into fuel briquette can solve waste disposal problem as well as can serve as an alternative energy source. The objective of this study was to investigate the possibility of producing briquette from coir dust and rice husk blend without binder. During this study, a briquetting experiment was conducted with different coir dust and rice husk blends (i.e. coir dust and rice husk ratio of 80:20, 60:40, 50:50, 40:60, 20:80 and 0:100). Briquetting operation was performed using a die-screw press type briquetting machine. The briquettes were tested to evaluate their density, compressive strength, calorific value, burning rate and water vaporizing capacity and it was found that mixing ratio had a significant effect on the physical, mechanical and combustion properties of the coir dust-rice husk briquettes. Density, compressive strength and calorific value and water vaporizing capacity were increased with increasing mixing ratio while burning rate was decreased. Coir dust-rice husk briquettes with mixing ratio of 20:80 had higher density (1.413 g/cm3), compressive strength (218.4 N/cm2), calorific value (4879 kcal/kg), water vaporizing capacity (0.853 l/kg) and low burning rate (0.783 kg/hour) followed by the mixing ratio 40:60, 50:50, 60:40 and 0:100. The results indicate that coir dust and rice husk blend briquettes were found to have better overall handling characteristics over rice husk briquette. However, production of briquettes from coir dust and rice husk at mixing ratio of 50:50 was found to be more suitable for commercial application in terms of cost effectiveness.